VOLUNTARY JURISDICTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present article search to highlight increasing in acceptation of alternative dispute resolution, instead opposition from society, and evidence how beneficial the implantation of these can be for collective. On this way, will be evidence that current crisis of access to judicial services calls for alternative solutions. Therefore, considering specifically the crisis of access to the judiciary in the labor scope, will be explained that alternative dispute resolution are capable contributing to judicial actions decrease, also to treat conflicts with the most appropriate judicial services. So, to exemplify benefits that alternative dispute resolution brings to the judiciary and society, will be discussed the utilization of voluntary jurisdiction, as an alternative dispute resolution, on the labor sphere.